VARIASI PROPORSI AMPAS UBI KAYU TAK TERFERMENTASI dan ACI TERHADAP DAYA KEMBANG, DAYA SERAP dan KUALITAS SENSORIS RENGGINANG - Setiawati, Bernadetta Budi (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2015)
The aim of this research is to determine the best proportion of the unfermented cassava waste and cassava starch on development and adsorption power and sensory quality of cassava rengginang. The research method using a design structured factorially composed of two factors; the first was the added cassava waste consisting of five levels symbolised with (A) i.e. A1 = 30%, A2 = 40%, A3 = 50%, A4=60% and A5 = 70% and the second was the addition of cassava starch consisting of 5 levels symbolised with (C) i.e. C1=70%, C2= 60%, C3= 50%, C4 = 40% and C5= 30%. The observed variables are the sensory quality of the produced cassava rengginang including texture, colour, flavour and taste. The development power and the adsorption power were measured by comparing the perimeter and weight of the crude(unprocessed) and the fried (processed) cassava rengginang respectively. The cassava rengginang that is most preferred by the panellists with the highest development power off 61,49% is the combination of A2 C2 using a proportion between cassava waste and cassava starch of 40:60. The lowest oil adsorption power of 34,55% is shown by the combination of A1C1 with a proportion between cassava waste and cassava starch of 30:70 while for the sensory quality of texture, flavour and taste is shown by the combination A2C2 with a proportion between cassava waste and cassava starch of 40:60, whereas concerning the colour, the combination A1C1 is most preferred with a proportion between cassava waste and starch of 30:70.